2009
DOI: 10.1007/s11162-009-9145-8
|View full text |Cite
|
Sign up to set email alerts
|

International and Citizen Faculty in the United States: An Examination of their Productivity at Research Universities

Abstract: The study examined the differences between international and U.S. citizen faculty members' productivity in the areas of research, graduate and undergraduate teaching, and service at research universities in the United States. Utilizing the 2004 National Study of Postsecondary Faculty (NSOPF:04) data set, we used a Structural Equation Modeling (SEM) to address the primary research questions in the study. The results indicated that international faculty members were significantly more productive in research, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 47 publications
4
96
1
Order By: Relevance
“…This situation has enabled to reach a judgment that the hypothesis established in this research has been supported. This situation coincides with the previous studies (Mamiseishvili & Rosser, 2010;Lauring & Selmer, 2010).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This situation has enabled to reach a judgment that the hypothesis established in this research has been supported. This situation coincides with the previous studies (Mamiseishvili & Rosser, 2010;Lauring & Selmer, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Looking at 16 sections of three universities in Denmark, Lauring and Selmer (2010) found that cultural diversity has a positive influence on satisfaction and performance. More relevant to this research, Mamiseishvili and Rosser, (2010) have found that international diversity had a positive impact on performance. Based on the theories and studies above, the following hypothesis has been developed.…”
Section: Cultural Diversity-performance Relationshipmentioning
confidence: 76%
“…A few studies examine foreign academics working in the UK (Gimenez and Morgan 2017). Overall, these studies on USA and UK examine issues such as cultural adaptation, work productivity (Mamiseishvili and Rosser 2010;Franzoni et al 2014), job satisfaction and coping mechanisms (Collins 2008;Romanowski and Nasser 2015), and faculty retention (Lawrence et al 2014). Well-established higher education systems naturally attract scholars from around the world without the need to actively recruit internationally.…”
Section: The Context Of Higher Educationmentioning
confidence: 99%
“…The most popular or commonly used measure of publication productivity is the number of published articles in journals (Creswell 1985;Mamiseishvili & Rosser 2010). The most recent measurement is the qualitative nature of publication productivity, such as publication in peer-reviewed journals (Print & Hattie 1997).…”
Section: Publicationmentioning
confidence: 99%